Evaluation of two molecular methods for the detection of Yellow fever virus genome - Nunes, Marcio R.T.; Palacios, Gustavo; Nunes, Keley N.B.; Casseb, Samir M.M.; Martins, Lívia C.; Quaresma, Juarez A.S.; Savji, Nazir; Lipkin, W. Ian; Vasconcelos, Pedro F.C. (Journal of virological methods, 2011)
Yellow fever virus (YFV), a member of the family Flaviviridae, genus Flavivirus is endemic to tropical areas of Africa and South America and is among the arboviruses that pose a threat to public health. Recent outbreaks in Brazil, Bolivia, and Paraguay and the observation that vectors capable of transmitting YFV are presenting in urban areas underscore the urgency of improving surveillance and diagnostic methods. Two novel methods (RT-hemi-nested-PCR and SYBR® Green qRT-PCR) for efficient detection of YFV strains circulating in South America have been developed. The methods were validated using samples obtained from golden hamsters infected experimentally with wild-type YFV strains as well as human serum and tissue samples with acute disease.